Formacja alumnów wyższych seminariów duchownych do korzystania ze środków społecznego przekazu w misji Kościoła - Domaszk, Arkadiusz (Prawo Kanoniczne, 2008)
The formation of students of higher theological seminaries embraces different problems. It is no possible to skip the mass-media problem in the seminarformation. The present research undertakes the problem of the seminar-formation in relation to using media in the mission of the Church, which are propositions of law and church-teaching in this field. Detailed norms of the education of seminarists bear upon three levels: first embraces the formation of seminarists as receivers, the next stage possesses the pastoral dimension, and the third (specialistic) is directed to those who will committing their future working on the field of media or will be lecturers in this sphere. The study of the documents of the church, instructions and propositions of law, confirms the urgent need of formation of the seminarists of theological seminaries, in the area of instruments of social communication. In the preparation of seminarists, one cannot only bring the separate lecture on the subject massmedia. Necessary is the general philosophical reference, and the theological formation to the present problems of social communication. In the present evangelization one ought to use mass-media. One ought today to ask after this, as to using instruments of social communication, which forms of the communication and which technologies are most useful in the concrete realization of the mission of the Church. One future priest, the conscious and critical receiver, should be a partner in the dialogue in the subject of present forms of the communication.